Foresight, participation and inclusion in public policies: The role of Future Scenario Workshops (FSW) - Alcalde Vargas, Gonzalo (2019)
The potential contribution of foresight techniques to more inclusive and participatory policymaking processes has been recognized in recent years, despite the fact that these tools were used originally in the upper levels of the state and private firms. This article presents a conceptual framework to understand the scope of this incipient contribution to development, the characteristics of a participatory foresight methodology that has been applied in Peru (TEF, for its Spanish initials), and a case that illustrates its implementation.